2003
DOI: 10.1007/s00101-002-0440-4
|View full text |Cite
|
Sign up to set email alerts
|

Anästhesie zur Sectio caesarea

Abstract: When compared with methohexitone, sevoflurane and N(2)O for caesarean section, initial total intravenous anaesthesia with esketamine and methohexitone mediated specific antinociception without negative maternal or fetal effects and not taking invasion kinetics or elimination between uterotomia and cord cutting into consideration. Avoidance of N(2)O allows optimal oxygenation of the fetomaternal unit. Stress protection and hemodynamic responses were well balanced, and intraoperative recall or negative dream rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…[7] Compared with opioids, esketamine has no significant effect of respiratory inhibitory, so it is used in pediatric anesthesia, obstetric anesthesia and auxiliary analgesia. [8] The results of this study showed that postoperative analgesia combined with esketamine can significantly reduce the amount of sufentanil and effective presses, and high-dose esketamine was significantly superior to medium and low doses. In addition, the rate of postoperative rescue analgesia and the occurrence of nausea and vomiting in the test group were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 92%
“…[7] Compared with opioids, esketamine has no significant effect of respiratory inhibitory, so it is used in pediatric anesthesia, obstetric anesthesia and auxiliary analgesia. [8] The results of this study showed that postoperative analgesia combined with esketamine can significantly reduce the amount of sufentanil and effective presses, and high-dose esketamine was significantly superior to medium and low doses. In addition, the rate of postoperative rescue analgesia and the occurrence of nausea and vomiting in the test group were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 92%
“…Esketamine can stimulate the sympathetic nervous system and increase blood pressure and heart rate, especially when given in high doses. 31 In the study by Zhang et al, 27 use of low-dose esketamine (0.15 mg/kg) was associated with a decreased incidence of hypotension during spinal anesthesia for cesarean delivery. It is therefore recommended that ketamine and esketamine should be considered for women undergoing elective cesarean delivery and at a high risk of hypotension.…”
Section: Discussionmentioning
confidence: 97%
“…Maternal hypotension frequently occurs during epidural anesthesia for cesarean delivery and, if severe, will lead to adverse maternal or fetal outcomes. Esketamine can stimulate the sympathetic nervous system and increase blood pressure and heart rate, especially when given in high doses . In the study by Zhang et al, use of low-dose esketamine (0.15 mg/kg) was associated with a decreased incidence of hypotension during spinal anesthesia for cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mix 1.3-1.5 MAC sevoflurane (Maruishi Pharmaceutical Co., Ltd., Osaka, Japan) in oxygen (30%) to maintain anesthesia, with positive-pressure ventilation using Carestation 650 anesthesia system (General-Electric Medical System (China) Co., Ltd., Wuxi, China). About 3 min before surgery began, the research drug, 0.5 mg kg À1 esketamine (Jiangsu Hengrui Pharmaceutical Co. Ltd., Lianyungang, China), 15,16 or 0.125 μg kg À1 sufentanil, was administered intravenously. Fluids given were determined by the length of fasting and the weight of the patient.…”
Section: Interventionsmentioning
confidence: 99%